Some ranks of modules over group rings - Victor Bovdi; Leonid Kurdachenko; Бовді Віктор; Курдаченко Леонід; Bódi Viktor (Taylor and Francis Ltd., 2020)
Abstract. A commutative ring R has finite rank r, if each ideal of R is generated at most by R elements. A commutative ring R has the r-generator property, if each finitely generated ideal of R can be generated by R elements. Such rings are closely related to Prüfer domains. In the present paper, we investigate some analogs of these concepts for modules over group rings.
https://www.ingentaconnect.com/content/tandf/lagb/2020/00000049/00000003/art00022
Keywords: Dedekind domain; Prüfer domain; special rank; különleges rang